Penggunaan Model Pembelajaran Think Pair Share Dan Student Team Achievement Division Pada Pembelajaran Menulis Surat Pribadi Siswa Kelas VII SMPN 1 Cikampek - Purwanti, Siska; Pratiwi, Wienike Dinar; Mujtaba, Sahlan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The research is motivated by the facts that occur in the field, namely the lack of understanding of students in writing personal letters. In addition, there are still many teachers who use conventional learning models, namely lectures without involving students. Thus, researchers want to compare learning models that suit the needs of students, namely Think Pair Share and Student Team Achievement Division. This study aims to examine differences in the increase in the ability to write personal letters using Think Pair Share and Student Team Achievement Division. To answer the problem formulation, the researcher used a quasi-experimental non-equivalent pre-test post-test control group design method. The population in this study was class VII SMPN 1 Cikampek with purposive sampling and two classes were selected, namely class VII-3 (N=40) as the experimental class using the Student Team Achievement Division model and class VII-1 (N=40) as the experimental class. control class using the Think Pair Share model. Based on the results of data processing using SPSS 16 Software for Windows, it can be concluded that the Student Team Achievement Division model is better than Think Pair Share but there is no significant difference in results. It was obtained that the average pre-test scores of the two classes were relatively the same before being given treatment, namely 65.9 for the experimental class and 65.8 for the control class. Then the value of the experimental class post test is worth 82 and the control class is worth 80.7. Furthermore, the N-Gain value for the experimental class is 0.46 and the control class is 0.43. This means that there is no significant difference between the experimental class and the control class. That way the two models are indeed in accordance with the needs of students..